The Routledge Guide to European Political Archives : Sources since 1945. - Cook, Chris (Taylor and Francis, 2012)
This new publication, a sister volume to the highly-acclaimed Routledge Guide to British Political Archives, provides a wide-ranging survey of the non-governmental archive sources for historians of post-war Europe. It provides, within a single volume, a rich treasure trove of resources drawn from the archives of the member states of the European Union and beyond. These major archive resources range from the International Institute of Social History in Amsterdam to the Modern Records Centre at Warwick University, from the European University Institute at Florence to the Archive of Social Democr.